2006
DOI: 10.1152/ajpgi.00048.2006
|View full text |Cite
|
Sign up to set email alerts
|

Distinct mechanisms of acid-induced HCO3secretion in normal and slightly permeable stomachs

Abstract: . Distinct mechanisms of acidinduced HCO 3 Ϫ secretion in normal and slightly permeable stomachs. Am J Physiol Gastrointest Liver Physiol 291: G464 -G471, 2006. First published May 18, 2006 doi:10.1152/ajpgi.00048.2006.-We investigated the regulatory mechanism of acid-induced HCO 3 Ϫ secretion in the slightly permeable rat stomach after an exposure to hyperosmolar NaCl. Under urethane anesthesia, a rat stomach was mounted on a chamber and perfused with saline, and the secretion of HCO 3 Ϫ was measured at pH 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 32 publications
(73 reference statements)
0
15
0
1
Order By: Relevance
“…Consequently, it is not entirely surprising that sensory nerve activation also contributes to epithelial HCO 3 − secretion that mediates luminal H + neutralization (3,5,244,484). Pharmacologic blockade experiments also implicate prostaglandins (e.g., PGE 2 ) and NO in the HCO 3 − secretion induced by luminal acidification (5,475,485). There is some evidence indicating that acid induced HCO 3 − secretion in the duodenum is a result of an NO/PGE2 pathway (475).…”
Section: Gastric Mucosal Defense Against Acidmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, it is not entirely surprising that sensory nerve activation also contributes to epithelial HCO 3 − secretion that mediates luminal H + neutralization (3,5,244,484). Pharmacologic blockade experiments also implicate prostaglandins (e.g., PGE 2 ) and NO in the HCO 3 − secretion induced by luminal acidification (5,475,485). There is some evidence indicating that acid induced HCO 3 − secretion in the duodenum is a result of an NO/PGE2 pathway (475).…”
Section: Gastric Mucosal Defense Against Acidmentioning
confidence: 99%
“…The resistance of the gastric mucosa to acid has prompted the use of "barrier breakers" to increase acid diffusion into the interstitium. For example, hypertonic NaCl or bile salts are used to disrupt the mucus lining or antisecretory drugs used to inhibit acid secretion; both of which collapse the mucus HCO 3 − gradient (5,481,486). Figure 27 The acid sensing pathway leading to a neurogenic hyperemia and HCO 3…”
Section: Gastric Mucosal Defense Against Acidmentioning
confidence: 99%
“…In this process primary sensory afferent neurons activated by the back-diffusing acid play a crucial role, since sensory nerve endings can sense acid via acid sensing channel [60][61][62][63][64][65][66][67][68].…”
Section: Resultsmentioning
confidence: 99%
“…This response is mediated by primary sensory afferent neurons, namely if the mucosal barrier is disturbed or disrupted in the presence of luminal acid, the acid reaching the lamina propria stimulates spinal afferents. This stimulation will initiate the efferent-like function of primary afferents resulting in CGRP and NO formation and release that induces a prompt hyperaemia in the gastro-duodenal mucosa and bicarbonate (HCO 3 − ) secretion [60][61][62][63][64][65][66][67][68].…”
Section: Capsaicin-sensitive Primary Afferent Neuronsmentioning
confidence: 99%
“…We previously reported that the acid-induced secretion of HCO 3 Ϫ in the stomach was inhibited by the prior administration of L-NAME, an inhibitor of NO production as well as indomethacin (Aihara et al, 2005a, suggesting the involvement of endogenous NO in the response, in addition to PGs. Indeed, HCO 3 Ϫ secretion was stimulated by the NO donor NOR-3 in the rat stomach and duodenum, and these actions were significantly attenuated by indomethacin (Sugamoto et al, 2001;Aihara et al, 2005bAihara et al, , 2006. In the present study, we showed that the response to NOR-3 in the mouse stomach was significantly attenuated by the prior addition of methylene blue, an inhibitor of guanylate cyclase as well as indomethacin, suggesting the mediation of this response locally by PGs and intracellularly by cGMP.…”
Section: Discussionmentioning
confidence: 99%